Physicochemical parameters and sensory properties of honeys from Buenos Aires region - Silvano, Maria F. (2014)
The physicochemical parameters (moisture, hydroxymethyl furfural, colour, electrical conductivity, free acidity, glucose, fructose and sucrose) and the sensory properties(aroma, taste, appeareance, texture) were determined in honeys from apiaries of the agricultural, hills and meadow zones of the south east region of Buenos Aires province (Argentina). The analysis of variance showed significant differences among zones in the mean value of hydroximethyl furfural, colour, electrical conductivity and sucrose content. The principal component analysis explained the 70% of the variance among samples with the first two principal components in both cases. The cluster analysis and linear discriminant analysis showed that samples were grouped in relation to the sampling region coinciding with the results of the principal component analysis. Results suggest that could be possible to classify honeys according to the geographic origin based on the physicochemical parameters; however, the sensory properties were not good predictors.